Diversity of plant resources used by family farmers in Altamira, Pará (Research, Society and Development, 2024)
His study aimed to identify the diversity of plant resources used by family farmers in the Assurini Settlement Project, in Altamira Municipality, Pará State, Brazil. The research was done in the Dispensa community and Gorgulho da Rita area, with 17 families interviewed between October 2023 and March 2024. Families use plant resource diversity in their family dynamics, with 131 plant species cited. The species are obtained from different locations, such as backyards (67.93%), with an incidence of fruit and medicinal plants, in farms (11.45%), in secondary forests (11.45%), and in forests (9.6%). These species are used for medicinal, food, and other purposes, such as equipment manufacturing used on the farms. We think it’s important to publicize the importance of maintaining and preserving this knowledge that contributes to the quality of life, families' food security, and biodiversity in the Settlement.